Production of the seed germination stimulant karrikinolide from combustion of simple carbohydrates - Flematti, G.; Scaffidi, A.; Dixon, Kingsley; Smith, S.; Ghisalberti, E. (2011)
The naturally occurring seed germination stimulant karrikinolide is formed from the combustion of plant material including cellulose. It has previously been reported that combustion of simple carbohydrates such as d-glucose does not produce extracts containing karrikinolide. Moreover, it was reported that extracts with germination-promoting ability could be obtained only by combustion of simple carbohydrates in the presence of amino acids such as l-glycine. By employing a 13C-labeled karrikinolide to physically quantify natural karrikinolide, we now show that it is produced from combustion of simple carbohydrates in similar amounts regardless of whether l-glycine is present or not. The addition of l-glycine appears to be beneficial in reducing the inhibitory effect of smoke extracts and provides a greater concentration range for effective germination-promoting activity.